ANALISIS TINGKAT KESEHATAN KOPERASI SIMPAN PINJAM PADA KPRI SEKOLAH DI KOTA PEKANABARU - Wijayanti Wijayanti; Syakdanur Nas; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to assess the health level of savings and loan cooperatives at KPRI Sekolah in Pekanbaru City based on Minister of Cooperatives and SMEs Regulation Number 14/M.KUKM/XII/2009, including capital, productive asset quality, management, efficiency, liquidity, independence and growth , and cooperative identity. The method used in this study is descriptive method, data obtained from documentation data in the form of financial statements for 2 years. The population in this study was KPRI School in Pekanbaru City which has a savings and loan business. The sampling technique using purposive sampling is the determination of samples based on certain considerations or criteria so that 5 (five) research samples are obtained. The results showed that the calculation of seven aspects of KPRI Schools in Pekanbaru City, the health level of cooperatives in 2016 from the number of 5 KPRI Schools, which received quite healthy predicate categories were 5 (five) KPRI Schools with a score of 60<x<80. Whereas in 2017 from the number of 5 (five) KPRI Schools studied, 2 (two) KPRI Schools received a healthy category namely KPRI SMPN 21 with a score of 83 and KPRI Karya SMAN 7 with a score of 83.25, which was healthy score of 80<x< 100, while 3 (three) KPRI Schools received a fairly healthy prediicate category, namely KPRI SMPN 13 with a score of 78.4, MAN 1 a score of 75.25, and MAN 2 & MTsN with a score of 75.4, where the predicate was quite healthy at a score of 60<x<80.Key Words: Health of cooperatives, savings